2021
DOI: 10.1111/1745-9125.12291
|View full text |Cite
|
Sign up to set email alerts
|

Public fear of protesters and support for protest policing: An experimental test of two theoretical models*

Abstract: As protests erupted across the United States in recent years over racialized issues (e.g., Black Lives Matter and Confederate monuments), so too did questions about when and how police should respond. Understanding public attitudes toward protest policing is important for police legitimacy and policy. One theory is that citizens are willing to trade civil liberties, such as the right to assemble, for security, and thus disruptive or dangerous protest tactics should increase support for police control by elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 118 publications
0
41
0
Order By: Relevance
“…6 Like other firms that source from opt-in online panels (e.g., YouGov, Qualtrics), Lucid provides researchers with quota samples of respondents that match U.S. census margins on demographic characteristics, and Lucid's quota samples compare favorably with nationally representative samples on both demographics and psychological traits (see Coppock & McClellan, 2019). As with other recent surveys that rely on quota samples to study criminal justice attitudes (e.g., Graham et al, 2020;Metcalfe & Pickett, 2021), we find that our estimates of key outcome measures, such as support for police abolition (23%), defunding (34%), and reform (66%), closely match those obtained from probability samples conducted in the preceding months. 7 For example, an ABC News/Ipsos poll from June 2020 found that 34% of U.S. adults supported defunding police departments (Jackson & Newall, 2020); and a Gallup poll from July 2020 found that 58% believed major police reforms were needed, though only 15% supported abolishing police departments (Crabtree, 2020).…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Like other firms that source from opt-in online panels (e.g., YouGov, Qualtrics), Lucid provides researchers with quota samples of respondents that match U.S. census margins on demographic characteristics, and Lucid's quota samples compare favorably with nationally representative samples on both demographics and psychological traits (see Coppock & McClellan, 2019). As with other recent surveys that rely on quota samples to study criminal justice attitudes (e.g., Graham et al, 2020;Metcalfe & Pickett, 2021), we find that our estimates of key outcome measures, such as support for police abolition (23%), defunding (34%), and reform (66%), closely match those obtained from probability samples conducted in the preceding months. 7 For example, an ABC News/Ipsos poll from June 2020 found that 34% of U.S. adults supported defunding police departments (Jackson & Newall, 2020); and a Gallup poll from July 2020 found that 58% believed major police reforms were needed, though only 15% supported abolishing police departments (Crabtree, 2020).…”
Section: Data and Resultsmentioning
confidence: 99%
“…A second possibility, distinct from views about policy slogans, is that opposition reflects negative beliefs about, or attitudes towards, the activists associated with these proposed changes to policing. For example, survey experimental work conducted after Floyd's murder found certain protest tactics that led to increased public fear (e.g., property destruction) also caused an increase in public support for repressive policing (Metcalfe and Pickett, 2021). Despite the fact that protests in 2020 were overwhelmingly peaceful (Armed Conflict Location and Event Data Project, 2020), selective media coverage of certain events (e.g., burning buildings in Minneapolis-Saint Paul) may have cultivated misperceptions that protestors and the movements associated with them were violent (Harlow, Kilgo, Salaverría, and García-Perdomo, 2020).…”
Section: The Relationship Between Public Opinion and Criminal Justice Policymentioning
confidence: 99%
“…Prior criminological research on racial attitudes has, instead, focused on the related notions of “racial resentment” and “racial animus” (i.e., the degree to which people blame or hold Black persons responsible for their group's unequal position in society; Drakulich et al. 2021; Riley & Peterson, 2020; Metcalfe & Pickett, 2021; Unnever & Cullen, 2010). Building on the seminal work of Kinder and Sears (1981), measures of racial resentment foreground agreement with statements such as “Black persons should try harder,” “Black persons are no longer discriminated against,” “Black persons benefit from undeserved advantages,” and “Black persons should work their way up without special favors like other groups did” (Riley & Peterson, 2020).…”
Section: The Mediating Role Of Systemic Racism Beliefsmentioning
confidence: 99%
“…While the public tends to be more supportive of peaceful policing tactics, recent research suggests that public perceptions of protest policing depends on situational characteristics and the goals of the protest (e.g. Black Lives Matter, pro-confederate monuments, see Metcalfe & Pickett, 2021). Specifically, in situations where protestors were armed, committed violence and property damage, and interrupted traffic, respondents were more likely to fear protestors and support aggressive policing tactics.…”
Section: Protest Policing and Attitudes Toward The Policementioning
confidence: 99%
“…The use of excessive force or repressive tactics against protestors violates these principles and can damage the trustworthiness of police (Curtice & Behlendorf, 2021;Nägel & Lutter, 2021;Perry et al, 2017). Research that has used disaggregated measures of perceptions of police and legitimacy has found that the use of excessive force and violence during protests is associated with declines in perceptions of police fairness, feelings of obligation to obey, and normative alignment with police (Curtice, 2021;Metcalfe & Pickett, 2021).…”
Section: Protest Policing and Attitudes Toward The Policementioning
confidence: 99%